Innovative Learning Models in Improving the Spirituality of Higher Education Students in Indonesia and Malaysia - Ahmad Fatah Yasin; Samsul Susilawati; Triyo Supriyatno; Zaidatun Tasir; Rika Inggit Asmawati; Abdulloh Chakim; Candra Avista Putri (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The transformation of higher education in the digital era encourages the implementation of innovative technology-based learning models across countries, including Indonesia and Malaysia. This study aims to identify innovative learning models applied at Maulana Malik Ibrahim State Islamic University, Malang, Indonesia, and Universiti Teknologi Malaysia, and to analyse their contributions to improving student spirituality. The research uses a descriptive qualitative approach through case studies, with data collected through interviews, observations, and documentation. The data are analysed thematically through the processes of data reduction, presentation, and verification. The results of the study show that both institutions develop technology-based learning that not only supports academic achievement but also strengthens students’ affective aspects, especially spirituality. Maulana Malik Ibrahim State Islamic University Malang implements explicit integration of Islamic values into every digital learning component. At the same time, Universiti Teknologi Malaysia develops a contextual approach through value reflection and spiritually based projects. Lecturers at both institutions play a key role in guiding the use of technology for contemplation and character-building. These findings confirm that with the right pedagogical approach, technology can be an effective medium in strengthening students’ spiritual values in higher education.